A collaborative energy sharing optimization model among electric vehicle charging stations, commercial buildings, and power grid. (1st November 2018) - Quddus, Md Abdul; Shahvari, Omid; Marufuzzaman, Mohammad; Usher, John M.; Jaradat, Raed
Highlights: A collaborative decision model to study energy sharing among buildings and charging stations. A customized solution approach to solve the optimization model in a realistic-size problems. Managerial insights drawn for decision makers to design an efficient collaborative scheme. Abstract: This paper studied a collaborative decision model to optimize electricity flow among commercial buildings, electric vehicle (EV) charging stations, and the grid under power demand uncertainty. We propose a two-stage stochastic programming model that realistically captures different operational constraints between multiple commercial buildings and EV charging stations. We developed a customized solution approach based on Sample Average Approximation method that can solve the proposed model efficiently and accurately. Finally, a real-life case study is constructed that draws managerial insights into how different key input parameters (e.g., grid power unavailability, power collaboration restriction) affect the overall energy network design and cost.